Trade frontiers & the birth rate - three universal preconceptions - Guilmette, Jean H. (Technical Centre for Agricultural and Rural Cooperation, 1989)
Jean H. Guilmette, who has just taken over as Director of the Club du Sahel, is a man who has made development the vocation. He is a French-speaking Canadian and a sociologist specialising in the administration of development programmes He was...